(untitled) (Italian Review of Legal History, 2020)
The law codes of the Gibichung rulers of Burgundy can be placed in very specific political contexts (c.500 and 517), but they can also be seen as legislation issued by late-Roman magistri militum, on the advice of members of the Gallo-Roman senatorial aristocracy, including Sidonius Apollinaris.